Association Between Age and Gender of Patients Underwent Tooth Whitening procedure - PERIYASAMY, YASHILA; SELVAM, DEEPAK; CHANDRASEKAR, SUBHASHINI (The journal of contemporary issues in business and government, 2021)
Tooth whitening has become one of the most frequently requested dental procedures by the public and the public has come to demand more whiter teeth, and a perfect smile. These include home-based products such as toothpastes, gels, and in-office based highly concentrated bleaching agents are applied under professional supervision. The profession and public have been aware of certain risks related to tooth whitening such as increased tooth sensitivity and gingival irritation. New research has shown that there are other risks such as tooth surface roughening, increased potential for demineralization, degradation of dental restorations, and unacceptable color change of dental restorations. The research is also focused on optimizing whitening procedures to reduce tooth sensitivity and to increase the persistence of the whitening. The aim of the study is to find the association between age and gender of patients undergoing tooth whitening. A total of 89000 cases were reviewed between June 2019 to March 2020 for teeth whitening procedure. A sample size of 30 case sheets were reviewed and data was analysed using SPSS software. The results were represented in the form of graphs. Chi Square was done to find the association between age and gender of patients who had undergone tooth whitening procedure and association was found to be statistically not significant (p>0.05). However there the association between the age and gender of the patient and type of bleaching procedure was found to be statistically significant (p<0.05). There are various treatment modalities available for tooth whitening. Dentists should educate patients about the benefits and risks of different whitening methods based on the current research and to suggest the best treatment option based on a correct diagnosis.